ASUHAN KEPERAWATAN PADA PASIEN MIOMA UTERI DENGAN ANSIETAS POST OP. HISTEREKTOMI - Agustin, Nurul (Jurnal Medicare, 2025)
Uterine myoma or fibroid is a type of benign tumor that develops from the smooth muscle tissue of the female uterus. Treatment of uterine myoma with clinical symptoms is generally carried out through a surgical procedure called hysterectomy (removal of the uterus). Postoperative patients often experience anxiety influenced by various factors, including persistent pain, concerns about the recovery process, uncertainty regarding home care, and changes in performing daily activities. This study aims to provide nursing care to patients with uterine myoma experiencing postoperative anxiety after hysterectomy, so that patients and their families can become more independent in preventing, improving, and maintaining the health of themselves, their families, and their environment to achieve optimal well-being at Jombang General Hospital (RSUD Jombang). This research employed a case study method involving two uterine myoma patients with postoperative hysterectomy anxiety, conducted over 3 days at RSUD Jombang. The results showed that the anxiety of 2 patients was resolved after nursing care interventions and evaluations were carried out for 3 days.